Evaluation of Osteotomy Healing in Boxer Dogs Undergoing Tibial Plateau Levelling Osteotomy Using Two Radiographic Scoring Systems - Huerta, Yael; Filliquist, Barbro; Agnello, Kimberly A.; Syrcle, Jason A.; Chou, Po-Yen; Garcia, Tanya C.; Massie, Anna M. (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective The aim of this study was to (1) compare 5-point and 10-point bone healing radiographic scoring systems using postoperative tibial plateau levelling osteotomy (TPLO) radiographs and (2) determine whether Boxer osteotomy healing time differs from age-matched Labrador Retrievers.Study Design This was a multicentre retrospective study. Fifty-eight client-owned dogs undergoing TPLO (29 Boxers and 29 Labrador Retrievers) were included. Five board-certified surgeons evaluated the radiographs three independent times. Osteotomy healing approximately 8 weeks postoperatively was graded using previously reported 5-point and 10-point scoring systems and immediate postoperative radiographs were assessed for the presence of an osteotomy gap of ≥1 mm.Results Both scoring systems had good consistency among observers. Intraobserver consistency was good in three out of five observers using the 5-point system and in four out of five observers using the 10-point system. Boxers had significantly lower radiographic healing scores at 8 weeks postoperatively compared with Labrador Retrievers using both scoring systems (p ≤ 0.001). The presence of an osteotomy gap postoperatively resulted in significantly lower healing scores at 8 weeks using both scoring systems (p < 0.001) in both breeds.Conclusion No difference was found in inter- and intraobserver variability between scoring systems. Boxer dogs had lower healing scores at 8 weeks after TPLO compared with Labrador Retrievers. An osteotomy gap of ≥1 mm was associated with lower healing scores.
Keywords: Boxer dogs; tibial plateau levelling osteotomy; cranial cruciate ligament disease; bone healing; radiographic scoring system